Modeling of extra strengthening in gradient nanotwinned metals based on molecular dynamics - Yang, Zailin; Ding, Xiaoyang; Yang, Yong; Li, Minghe; Cao, Shihao (Frontiers in Materials, 2022)
Gradient nanotwinned metals exhibit extra strengthening and work hardening behaviors, which have enormous potential for engineering applications. In this study, molecular dynamics method is performed for analyzing the effects of nanotwinned structure gradient on uniaxial tensile loading behaviors of gradient nanotwinned metals. Results show that the elasticity, dislocation stored ability and dislocation evolution of the nanotwinned lamellar are affected by the surrounding nanotwinned structure. Moreover, we established a quantitative phenomenological plastic flow stress model for gradient nanotwin metals based on physical connotation, and discussed the effects of nanotwinned thickness and nanotwinned structure gradient on the strength. Particularly, the back stress associated with the nanotwinned structure gradient and the contribution of geometrically necessary dislocations to statistically stored dislocations is included in our model. The tensile response the theoretical model descripted is in good agreement with the experimental results. We hold the opinion that the promotion effect of geometrically necessary dislocations to statistically stored dislocations will not be manifested until the nanotwinned structure gradient reaches a critical value. This research provides guidance for the structural design of gradient nanotwinned metals.